Marriage and parent-child interaction state in the family functioning structure of women having paranoid schizophrenia - Дрюченко, Майя Олександрівна; Маркова, Маріанна Владиславівна (ScienceRise: Medical Science, 2017)
Aim. To analyze marriage and parent-child interaction state in the family functioning structure of women having paranoid schizophrenia (PS) for the further identification of possible aims of their psychological correction. Contingent and methods. 100 women, having PS, and their husbands were examined at psychiatric department of Zakarpattya oblast narcological dispensary during 2014 – 2016. The women were aged from 25 to 40 years, and the disease duration was from 2 to 15 years. The approximate age of the husbands did not exceed 7 years between them and their wives. 50 common families were examined as the reference group. The women were examined using clinical and psychopathological, and psychodiagnostic methods, the men – using clinical and psychological, and psychodiagnostic methods. Results. In result of research, substantial violations of marital and parent-child family functioning levels were found in families with women having PS; moreover, both the women with PS, and their husbands found significantly worse indexes concerning all components of this area, comparing to the healthy persons. In families, where the woman has PS, a sufficient deformation of the family interaction on the marriage (90 %) and parent-child (84 %) levels was found in 91 % of cases, which characterized by conflict and aggression high level, family functions ignoring by family members, the lack of attention to the children, the unwillingness to engage in their upbringing, high general level of neuroticism of the family members. In the other 9 %, the signs of family interaction distortion, which were out of its expressed violation indicators range, were found. Conclusion. The obtained data were used as a base for development of the system for medical and psychological measures for optimization of mother-child interaction in women with PS